Genome‐wide identification of microRNAs regulating the human prion protein. (21st December 2018) - Pease, Daniel; Scheckel, Claudia; Schaper, Elke; Eckhardt, Valeria; Emmenegger, Marc; Xenarios, Ioannis; Aguzzi, Adriano
Abstract: The cellular prion protein (PrP C ) is best known for its misfolded disease‐causing conformer, PrP Sc . Because the availability of PrP C is often limiting for prion propagation, understanding its regulation may point to possible therapeutic targets. We sought to determine to what extent the human microRNAome is involved in modulating PrP C levels through direct or indirect pathways. We probed PrP C protein levels in cells subjected to a genome‐wide library encompassing 2019 miRNA mimics using a robust time‐resolved fluorescence‐resonance screening assay. Screening was performed in three human neuroectodermal cell lines: U‐251 MG, CHP‐212 and SH‐SY5Y. The three screens yielded 17 overlapping high‐confidence miRNA mimic hits, 13 of which were found to regulate PrP C biosynthesis directly via binding to the PRNP 3'UTR, thereby inducing transcript degradation. The four remaining hits (miR‐124‐3p, 192‐3p, 299‐5p and 376b‐3p) did not bind either the 3'UTR or CDS of PRNP, and were therefore deemed indirect regulators of PrP C . Our results show that multiple miRNAs regulate PrP C levels both directly and indirectly. These findings may have profound implications for prion disease pathogenesis and potentially also for their therapy. Furthermore, the possible role of PrP C as a mediator of Aβ toxicity suggests that its regulation by miRNAs may also impinge on Alzheimer's disease.